Castles and cannons - Scoular Anderson (London; Orion Children's Books, 2017)
It's never too early to find out about kings and queens, drawbridges and dungeons, and old castle toilets with this brand new green Early Reader factbook. Early Readers are stepping stones from picture books to reading books, perfect for building confidence in new readers and reluctant readers. A green Early Reader is a first factbook. Did you know that the first castles were called motte and bailey castles? Or that there were holes above the castle gates called murder holes? Learn fascinating facts about life in a castle and how ancient castles were built and defended, in this brand new non fiction Early Reader from Scoular Anderson, with full colour illustrations on every page
Keywords: Juvenile works